Highlighting the Terroir Influence on the Aromatic Profile of Two Romanian White Wines - Diana Ionela Popescu (Stegarus); Oana Romina Botoran; Roxana Elena Ionete; Daniela Sandru; Nicoleta Anca Sutan; Violeta-Carolina Niculescu (Applied Sciences, 2023)
Climate conditions clearly influence the concentration of important substances in grapes, generating chemical reactions that will determine the final wine aromas. Three different regions were chosen to cover the most important viticultural areas from Romania. The aim of this study was to highlight, for the first time, the volatile profile for two Romanian white wines, Feteasca regala and Feteasca alba, from three different vineyards (Silagiu, Aiud, and Sarica Niculițel). The results showed that wine’s aromatic profile was directly proportional with the area of origin for the grapes, directly correlated to the climate. The obtained values for alcohols, esters, aldehydes, and terpenoid compounds were also related to the oenoclimatic aptitude index, a significant accumulation of aroma compounds being observed mainly for the Feteasca regala wine. A total of 17 superior alcohols were evidenced within the two types of wines, among them, 2-phenyl ethanol being distinguished by its higher level in all samples, varying from 7692 up to 11,783 µg/L. Together with some aromatic esters, it offers one of the most pleasant aromas, resembling rose flavour. Of all the acids found in wines, the succinic acid has the most intense flavour, tasting somehow bitter and salty, imprinting to wine a certain “juiciness” and “vinosity”. Diethyl succinate was one of the main esters in all six samples, with concentrations from 777 up to 1200 µg/L. Also, two terpenoid compounds and two aldehydes were found in all samples. The data obtained from PCA evaluation suggested that there is a significant variance among wine varieties. Nevertheless, hierarchical clustering was applied to explain the relationship between the six samples of wines, the smallest clusters that included Silagiu and Aiud winegrowing regions suggesting an increased similarity of the compositional profile.